2021
DOI: 10.4103/aca.aca_104_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ringer's lactate and plasmalyte-a as cardiopulmonary bypass prime for bypass associated acidosis in valve replacement surgeries

Abstract: Introduction: A wide range of acid base fluctuations are seen during Cardiopulmonary bypass (CPB) and the development of metabolic acidosis is well recognized. We conducted a study tocompare the metabolic effects of Ringer lactate and Plasmalyte-A as CPB prime in causing bypass associated acidosis in valve replacement surgeries. Methods: We performed a prospective, randomized controlled study on a total of 80 adult patients undergoing CPB for valvular heart surgeries. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
(12 reference statements)
0
3
1
Order By: Relevance
“…These changes suggested the development of metabolic acidosis in the Ringer Lactate group. Additionally, the Ringer Lactate group had a higher number of patients experiencing hypotension and arrhythmias, indicating a higher degree of acidosis and potential adverse effects [15]. In contrast, based on our results, as we found that lactate levels were significantly higher in the Ringer Lactate group, other parameters such as blood biochemistry, pulmonary function, renal function, bleeding, hemostasis, and other postoperative outcomes did not exhibit statistically significant differences between the Plasmalyte and Ringer Lactate groups.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…These changes suggested the development of metabolic acidosis in the Ringer Lactate group. Additionally, the Ringer Lactate group had a higher number of patients experiencing hypotension and arrhythmias, indicating a higher degree of acidosis and potential adverse effects [15]. In contrast, based on our results, as we found that lactate levels were significantly higher in the Ringer Lactate group, other parameters such as blood biochemistry, pulmonary function, renal function, bleeding, hemostasis, and other postoperative outcomes did not exhibit statistically significant differences between the Plasmalyte and Ringer Lactate groups.…”
Section: Discussioncontrasting
confidence: 48%
“…There was significant hyperlactatemia with Ringer's lactate compared to Plasmalyte-A. The SID decreased during the CPB in the Ringer's lactate group (41.102 mEq/L at T1to 35.66 mEq/L [P = 0.033] at T2) in comparison to Plasmalyte-A group [15].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations